A bibliometric analysis of teachers' turnover intention in higher education - Danxin, Liang; Mohammed, Rosmah; Ab Rahman, Rozanah (Human Resources Management Academic Research Society (HRMARS), 2024)
The study of turnover intention has been concerned by scholars. This study examined trends in turnover intention publications and conducted a literature review. In this study, following the PRISMA diagram and using bibliometric methods to evaluate teachers' turnover intention, which using descriptive analysis and cluster analysis to analysis 82 selected articles and investigate its current situation, influencing factors and future research direction. The results of the analysis show that the number of publications on teachers’ turnover intention in higher education had a positive growth trend recently. It has grown dramatically since 2019, Frontiers in Psychology and Journal of Applied Research in Higher Education played significant roles.The United States is the country with the most publications and is also the most influential. It was followed by Malaysia, China, Pakistan and Malaysia. The results also show that turnover intention, job satisfaction and higher education are the most used keywords in teachers’ turnover intention literature. Future research areas identified based on VOSviewer will explore potential literature gaps in work engagement, work-family conflict, and work- family balance.